MORPHOMETRIC FEATURES OF THE SCLERA OF THE EYEBALL IN COMPLICATED MYOPIA (International journal of medical sciences, 2025)
In this article, the results of the study of the morphological status of scleromalacia in the sclera of the eyeball in developing myopia were a comparative assessment of the morphological characteristics of connective tissue, that is, the reaction of the sclera, the latter after the introduction of an experimental xenograft.